Estimation of the Fatigue Life of the Front Axle of a Truck - Prochowski, L. (Engineering Transactions, 1992)
Problems of dynamical loads and statistical characteristics of stresses in the front axle of a truck were considered. The probability of fatigue damages and the estimation of the fatigue life for various conditions of the vehicle's operation were calculated.